Monitoring change in land use and land cover in Rupnagar district of Punjab, India using Landsat and IRS LISS III satellite data - Kumar Singh, Chander; Shashtri, Satyanarayan; Mukherjee, Saumitra; Avtar, Ram; Kumar Singh, Sudhir (Ecological Questions, 2010)
Information about change is necessary for updating Land Use/ Land Cover LULC maps and the management of natural resources. The paper aims to map the changes in the LULC using hybrid classification methods and to quantify the land use/ land cover change that took place in the Rupnagar district of Punjab. The paper promotes the classification of LULC based on remote sensing information (obtained mainly through the utilization of Thematic Mapper TM) to generate data products that are both appropriate to, and immediately usable within different scientific applications. Satellite data provides the basis for geographically referenced land use/land cover characterization that is internally consistent, repeatable over time, and potentially more reliable. The main objective of this study is to quantify the change in the area of various LULC classes. Classification of four reflective bands of three Landsat images was carried out by using Isodata clustering algorithm with the aid of ground truth data. The second part focused on land use/ land cover changes by using the change detection comparison (pixel by pixel). The change analysis was performed by post image classification method, comparing the data from three different dates. The result indicates there was a rapid change in land use/land cover due to the increase in population. The results indicate that severe land cover changes have occurred in cropland (225.97 km2), dense forest (128.57 km2), settlement (93.5 km2), salt affected land (9.74 km2) and water body (11.69 km2) areas from 1989 to 2006.